TÜCAUM 2024 II. Coğrafi Bilgi Sistemleri Çalıştayı Raporu - Necla Türkoğlu; Rüya Bayar; İlker Alan; Zeynep Zobu; Saitcan Güngördü; Gönül Mutlu (Coğrafi Bilimler Dergisi, 2024)
Ankara University, Research Center of Turkish Geography (TUCAUM), dedicated to the 100th Anniversary of Republic, organized the "2nd Geographic Information Systems Workshop and Project Competition" on March 7, 2024, at the Faculty of Language and History-Geography. In this workshop, which was organized to bring together the public, private sector and academia under the umbrella of Geographic Information Systems (GIS), to share studies and developments on the subject and to reinforce mutual cooperation, 21 participants who are experts in their fields made presentations. 19 poster presentations prepared by undergraduate and graduate geography students from universities in different provinces and geographers who have recently joined the profession and working life were evaluated in the project competition, and the awards were presented to the winners by TUCAUM, Başarsoft, Esri Türkiye and Netcad. The purpose of this report is to reveal the issues discussed, identified issues and interactions at the TUCAUM 2024 2nd Geographic Information Systems Workshop, which brought together a large audience with more than 200 participants.